The Role of Workers Unions in the Effort to Fight for the Rights and Obligations of Workers in Companies Declared Bankrupt In Indonesia - Yusman Yusman; Annissa Rezki; Nur Rohim Yunus (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
A trade union is a group of workers who band together to promote, protect, and improve their members' social, economic, and political interests through collective action. A trade union is a workers' organization formed to defend the destinies of workers. In the world of work, there are two parties, namely workers and employers. Workers/labourers as citizens have equal position in the law, the right to get a decent job and livelihood, express opinions, gather in one organization, and establish and become members of a trade/labour union. The right to freedom of association has also been recognized by the international community. Settlement of disputes between business actors cannot be separated from the application of business ethics which is an inseparable part of the business law environment and business practices itself. This writing uses a qualitative methodology, which in its translation will make it easier for the writer to analyze and convey the intent and purpose of writing that has been adjusted to the author's background and goals.